The fight for Asian American civil rights: liberal protestant activism, 1900-1950 - Griffith, Sarah Marie (University of Illinois Press, 2018)
"We must fight for the Lord and Japan": Christian internationalism in the Pacific -- A splendid storehouse of facts: establishing the survey of race relations on the Pacific coast -- Once I was an American: Asian North American resistance in the interwar period -- A new Pacific community: debating equality in the interwar period -- "The injustice of internment": expanding coalitions in the internment era -- The legacies of a movement -- Epilogue